Typology of Use of Plant Growth Regulators by Farmers in Wonorejo Village, Malang-Indonesia - Budiyanto, Moch. Agus Krisno; Aminah, Tien; Husamah, H. (RA Journal of Applied Research, 2021)
In an effort to increase the growth of plants, in general, farmers use growth regulator substances such as auksin, giberelin, and cytokinin. In an effort to analyze the behavior of plant growth regulator (PGRs), the purpose of this research is to analyze the typology of plant growth regulator. The research design used is descriptive qualitative. The research informant is 10 a member of Organic Farmer Group of Sumber Urip-1 Wonorejo Village, Poncokusumo Subdistrict, Malang District. The sampling technique used is purposive sampling. Data collection methods used were in-depth interviews and participant observation. Data analysis used in this research is qualitative analysis by content analysis by using Interactive Model from Miles and Huberman. In this study, magna findings or concepts about the use of plant growth regulators will be analyzed based on the Social Movement Typology theory. Based on the results of the study can be concluded that the use of plant growth regulators included in Alternative Social Movement Typology.